2015
DOI: 10.12933/therya-15-304
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution of the ocelot (Leopardus pardalis) in Northeastern Mexico

Abstract: Introduction:The ocelot (Leopardus pardalis) is a Neotropical cat which is threatened by illegal hunt and habitat destruction in the Mexican territory. Mexican and American authorities are interested in promoting their conservation. The MaxEnt algorithm allows modeling the potential distribution of elusive species, for instance, the ocelot. This has been based on trustable presence records and some other information about the habitat condition. This work was developed with the aim of generating important infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…As Ghoddousi et al (2020) identified, ignoring human–wildlife conflicts when identifying corridors may result in funneling dispersing individuals into ecological traps if dispersing through human‐dominated regions increases mortality. Conditions in far northeastern Mexico adjacent to Texas are believed unsuitable for ocelots (Martínez‐Calderas et al 2015, Ocañas‐García et al 2018), meaning dispersing ocelots from south Texas would have to safely travel about 300 km to join the Tamaulipas population of ocelots in northeastern Mexico. In addition to elevated risk of mortality involved by crossing numerous highways, a dispersal of this distance would be unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…As Ghoddousi et al (2020) identified, ignoring human–wildlife conflicts when identifying corridors may result in funneling dispersing individuals into ecological traps if dispersing through human‐dominated regions increases mortality. Conditions in far northeastern Mexico adjacent to Texas are believed unsuitable for ocelots (Martínez‐Calderas et al 2015, Ocañas‐García et al 2018), meaning dispersing ocelots from south Texas would have to safely travel about 300 km to join the Tamaulipas population of ocelots in northeastern Mexico. In addition to elevated risk of mortality involved by crossing numerous highways, a dispersal of this distance would be unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used habitat‐suitability models to predict the distribution of small and medium Neotropical felids using climatic and topographic information as a proxy for habitat characteristics (Cuyckens, ; Espinosa et al., ; Martínez‐Calderas et al., , ). However, for studies conducted at regional or more bounded scales, where climatic variability is minimal, other factors may became more relevant for predicting and understanding current species distributions (Elith & Leathwick, ; Scheldeman & van Zonneveld, ), especially when focusing on human‐modified landscapes and species affected by human persecution like the carnivores in the Atlantic Forest (De Angelo, Paviolo & Di Bitetti, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study on the southern edge of the ocelot's range in Brazil, Araújo et al (2021) found temperature and precipitation variables to be important in their study: mean temperature of the wettest quarter (BIO8, the third most important variable in this study), precipitation of the coldest quarter (BIO19, the least important variable in this study), and temperature annual range (BIO7, not included in this study due to correlations). In a related study in northeastern Mexico, Martínez-Calderas et al (2015) found three climatic variables to be important in explaining ocelot distribution: precipitation during the wettest month (BIO13, the fourth most important variable in this study), precipitation during the wettest quarter (BIO16, not included in this study due to correlations), and precipitation during the coldest quarter (BIO19, the least important variable in this study). Differences between our paper and the two previous studies may have been in part due to methodological differences in how variable importance was calculated.…”
Section: Discussionmentioning
confidence: 51%
“…By using occurrence data collected across the entire geographic range of the ocelot, our ensemble model likely more accurately represents the range of bioclimatic conditions in which this species can persist. The two earlier studies incorporating climate predictors of ocelot distribution were conducted in regional geographies, one in northeastern Mexico (Martínez-Calderas et al, 2015) and one in southern Brazil (Araújo et al, 2021), toward the geographic peripheries of the ocelot's range. By including the whole of the species' range, our study is better able to tease out the climatic associations with ocelot occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation